(3YfhGf GdfaGSI aj TQM OjhGf GdMeGSIs - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3hbGd jMji Hf efUhQ GdPgdj, hJQhi dehSi Hf LGHQ GdMfaj GdPgd aj GdCUd GdbWYI ef Gddjd(B: (3hLOfG CHGfG Ydi Md HHdOI oShi Hjf bjS bjS YjdGf hGdaRQ s
(3BNQgG (B:s
(3hgfG GdHdbYI HeYfi Whd ecKg ajgG gfG GfJgi GdfUa GdChd ef TQM GdMeGSI HMeO Gddg JYGdi s
(3Chd GdehLhO efgGs
(3HOAkG ef U (B127s
(3ef bHd HGH GdeQGKjs
(3hHgG fXGe GdJYbjHI s
(3fSNI KGfjI GdfUa GdChd s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs